2006
DOI: 10.1021/ac0612426
|View full text |Cite
|
Sign up to set email alerts
|

Development of a “Membrane Cloaking” Method for Amperometric Enzyme Immunoassay and Surface Plasmon Resonance Analysis of Proteins in Serum Samples

Abstract: Detection of trace amounts of target proteins in the presence of high concentrations of matrix proteins (e.g., serum samples) without separation steps is of great significance to biomedical research but remains technically challenging. Here we report a "membrane cloaking" method to overcome nonspecific protein adsorption and fouling problems for label-free surface plasmon resonance detection and heterogeneous immunosensing. A thin, hybrid, self-assembled monolayer on gold was formed with 70 mol % mercaptopropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…26 A membranecloaking methodology was recently developed to remove nonspecific adsorption after a sample was exposed to biological fluid, without disrupting the biomarker bound to the molecular receptor. 27 In spite of these results, the mechanism of protein adsorption is not clearly understood. 28 It is suggested that different proteins consecutively adsorb at surfaces, starting with the most prominent protein in serum, albumin, followed by larger proteins such as IgG and fibrinogen.…”
Section: Introductionmentioning
confidence: 99%
“…26 A membranecloaking methodology was recently developed to remove nonspecific adsorption after a sample was exposed to biological fluid, without disrupting the biomarker bound to the molecular receptor. 27 In spite of these results, the mechanism of protein adsorption is not clearly understood. 28 It is suggested that different proteins consecutively adsorb at surfaces, starting with the most prominent protein in serum, albumin, followed by larger proteins such as IgG and fibrinogen.…”
Section: Introductionmentioning
confidence: 99%
“…A similar experimental setup was used to monitor target DNA recognition using SPR and ACV concurrently, which allowed for optimal nucleic acid probe sequence selection from the optical and electrochemical data [106]. Cross-platform protein recognition, important in the field of immunosorbent assays (ELISA), has been successful via a “membrane cloaking” method that was developed for complementary results to be obtained by SPR and amperometric techniques [107]. Once antibodies were immobilized over a self-assembled monolayer, a cloaking phospholipid membrane was applied to the surface, which was resistant to nonspecific binding and could be removed once the assay was complete.…”
Section: Hyphenated Assays With Surface Plasmon Resonancementioning
confidence: 99%
“…This strategy was employed for the detection of undiluted serum spiked with IgG (Phillips et al 2007 ). A membrane cloaking strategy was designed to remove nonspecifi cally bound proteins on an SPR sensor, leaving only the analyte bound to the molecular receptor at the surface.…”
Section: Protein Sensingmentioning
confidence: 99%